2007
DOI: 10.1148/radiol.2453062061
|View full text |Cite
|
Sign up to set email alerts
|

Pure Ductal Carcinoma in Situ: Kinetic and Morphologic MR Characteristics Compared with Mammographic Appearance and Nuclear Grade

Abstract: http://radiology.rsnajnls.org/cgi/content/full/245/3/684/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
116
5
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 31 publications
19
116
5
9
Order By: Relevance
“…Prior publications have shown that DCIS with an area of AD occurs in about 7%-13% of the cases (40,41). In our study, the case of DCIS showed focal enhancement and DWI was negative, even though focal enhancement is usually the least common finding, being seen in only 1%-12% of cases (42,43). The reported sensitivity of MRI for the detection of DCIS is lower than that for the detection of invasive breast cancers.…”
Section: Discussioncontrasting
confidence: 52%
“…Prior publications have shown that DCIS with an area of AD occurs in about 7%-13% of the cases (40,41). In our study, the case of DCIS showed focal enhancement and DWI was negative, even though focal enhancement is usually the least common finding, being seen in only 1%-12% of cases (42,43). The reported sensitivity of MRI for the detection of DCIS is lower than that for the detection of invasive breast cancers.…”
Section: Discussioncontrasting
confidence: 52%
“…6,7,25 Although kinetic curve patterns represent the vascularity and stroma of lesions, benign non-mass-like lesions, such as mastopathy, can show either increased vascularity or stromal edema depending on the menstrual cycle or activity, which may thus lead to a false-positive result. 26 Another factor associated with false-negative results is a volume averaging eŠect due to contamination of the background tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to using a single diagnostic criterion (DCE-MRI or ADC value), combining the two (DCE-MRI and ADC value) increased both true-and false-positive cases. Four additional true-positive cases (Cases 17,25,26,27) were identiˆed by adding the ADC value to DCE-MRI, and 4 additional true-positive cases (Cases 13, 21, 22, 23) were identiˆed by adding DCE-MRI to the ADC value. On the other hand, one additional false-positive case (Case 10) was found by adding the ADC value to DCE-MRI, and 2 additional false-positive cases (Cases 1, 2) were found by adding DCE-MRI to the ADC value.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
“…A idade e o estado hormonal da paciente também devem ser levados em consideração 4 . Na ressonância magnética, o CDIS manifesta-se como um nódulo em apenas 14 a 41% dos casos [5][6][7] . Quando isso acontece, o nódulo aparece irregular, com margens irregulares ou espiculadas e realce heterogêneo.…”
Section: Discussionunclassified